Synthesis and evaluation of a novel analgesic conotoxin Lt7b that inhibits calcium currents and increases sodium currents. Issue 20 (1st September 2022) - Wu, Yun; Yang, Manyi; Li, Yubin; Zhang, Wei; Zhou, Maojun
Abstract: Conotoxins are promising neuropharmacological tools and drug candidates due to their high efficiency and specificity in targeting ion channels or neurotransmitter receptors. In this study, a novel O2 ‐superfamily conotoxin, Lt7b, was synthesized and its pharmacological functions were evaluated. Lt7b with three modified amino acids and three disulfide bonds was successfully synthesized. CD spectra showed that Lt7b had a typical α‐helix in the secondary structure. Patch clamp experiments on rat DRG neurons showed that Lt7b could significantly inhibit calcium currents with an IC50 value of 856 ± 95 nM. Meanwhile, 10 μM Lt7b could significantly increase the sodium currents by 77 ± 8%, but it had no obvious effects on the potassium currents in DRG neurons. In addition, patch clamp experiments on ion channel subtypes showed that 10 μM Lt7b could inhibit 7.0 ± 1.2%, 8.0 ± 1.5%, 4.6 ± 3.4%, and 9.5 ± 0.1% of the hCav 1.2, hCav 2.1, hCav 2.2, and hCav 3.2 currents, respectively, while it did not increase the rNav 1.7, rNav 1.8, hNav 1.5, hNav 1.7, and hNav 1.8 currents. Lt7b had no obvious toxicity to HaCaT and ND7/23 cells up to 1 mM and significantly increased the pain threshold at the testing time of 0.5–4 h in a dose‐dependent manner in the mouse hotplate assay. This novel conotoxin Lt7b may be a useful tool for ion channel studies and analgesic drug development.